C64 UNMASKING THE PREVALENCE OF AMYLOID CARDIOMYOPATHY IN THE REAL WORLD: RESULTS FROM PHASE 2 OF AC–TIVE STUDY, AN ITALIAN NATIONWIDE SURVEY. (18th May 2022) - Merlo, M; Pagura, L; Porcari, A; Cameli, M; Vergaro, G; Musumeci, B; Biagini, E; Canepa, M; Crotti, L; Imazio, M; Forleo, C; Cappelli, F; et al.
Abstract: Background: Clinicians need to identify patients with amyloid cardiomyopathy (AC) at an early stage, due to the availability of disease–modifying therapies. Some echocardiographic findings may rise the suspicion of AC, also in patients with mild or no symptoms, addressing second level diagnostic tests. Aim: To investigate the prevalence of AC in consecutive patients ≥55 years undergoing clinically indicated, routine transthoracic echocardiogram in Italy and presenting echocardiographic signs suggestive of AC. Methods: This is a prospective multicentric study conducted in Italy. It comprises two phases: 1) a recording phase consisting in a national survey on prevalence of possible echocardiographic red flags of AC in consecutive unselected patients ≥55 years undergoing routine echocardiogram (previously published) and 2) an AC diagnostic phase involving a diagnostic work–up for AC to investigate AC prevalence among patients with at least one echocardiographic red flag (herein presented). Patients that in Phase 1 presented an "AC suggestive" echocardiogram (i.e., at least one red flag of AC in hypertrophic, non–dilated left ventricles with preserved ejection fraction) underwent clinical evaluation, blood and urine tests and scintigraphy with bone tracer. Diagnosis of transthyretin related–AC (ATTR–AC) was made in presence of grade 2–3 Perugini uptake at scintigraphy and absence of monoclonal protein. The study was registered at ClinicalTrials.gov (#NCT04738266). Results: Of the 5315 screened echocardiograms, 381 exams (7.2%) were classified as "AC suggestive" and proceeded to Phase 2. 217 patients completed Phase 2 investigations. Main reasons for the 164 non–entering patients into Phase 2 were death (n = 49) and refusal to participate (n = 66). A final diagnosis of AC was made in 62 patients with an estimated prevalence of 28, 6% (95% CI: 22, 5%–34, 7%). ATTR–AC was diagnosed in 51 and AL–AC in 11 patients, ascertaining a prevalence of 23, 5% (95% CI: 17, 8%–29, 2%) and 5, 1% (95% CI: 2, 2%–8, 0%), respectively. Conclusion: Among a cohort of consecutive unselected patients ≥55 years with echocardiographic findings suggestive of AC, the prevalence of AC ranged from 23% up to 35%. Although ATTR–AC was predominant, AL–AC was diagnosed in a significant number of cases. Echocardiography has a fundamental role in screening patients, raising the suspicion of disease and orienting diagnostic work–up for AC.